Hydrosystem for integrated control of flood and low flow for a river Basin in Sarawak - Bong., Charles Hin Joo; Rosmina, Ahmad Bustami.; Salim, Said.; Putuhena, Frederik Josep (Universiti Malaysia Sarawak (UNIMAS), 2009)
Sungai Sarawak River basin is generally quoted as 1430 km2 in size and only 6% of the area is developed. Nevertheless, the catchment size is enormous (nearly the size of one Melaka State of 1650 km 2 ) and the river networks covers huge areas including some hard to reach topography. Due to this, Sungai Sarawak basin was chosen as research area. The following are achievements from the drawn studies: 1. By using regionalization technique, Sarawak was sub-divided into five flood frequency regions (FFR) and two mean annual flood regions (MAFR). Sungai Sarawak basin is located in FFR-1 and MAFR-2. With that, engineers could come out with flood estimation for a certain site within the Sungai Sarawak catchments, by multiplying the regional dimensionless flood frequency curve and the regional mean annual flood equation representing the site. 2. The existing 23 rainfall stations within Sungai Sarawak basin were subjected to pattern and frequency analyses to better understand the rainfall occurrence and characteristics in the basin. Monthly rainfall pattern analysis was carried out to determine the factors influencing the rainfall distribution in Sungai Sarawak basin. Meanwhile, rainfall frequency analysis was performed in reduced variate curves based on Gumbel distribution. 3. InfoWorks RS modeling software was applied to model the Sungai Sarawak systems. To this end, 7 models were developed to provide a platform for understanding of the river behaviors, its processes during high flow events and possible engineering solutions. Such computer models were proven a powerful tool to show "what would be happening" and then assisted decision making. 4. For low flow analysis, there is no critical time of dry season found. The volume of available water from the selected locations of Git and Buan Bidi are enough to provide water for the water demand of Kuching City. 5. Finally, Logical Framework Approach was demonstrated as the designing tool for outlining a proposed framework for achieving the Integrated Flood Management IV settings and objectives of a collaborative network among the responsible agencies. This framework was intended to serve as an interface for shaping a currently lacking basin based flood management in the capital city.